Pengaruh Gradasi Pasir Dan Kadar Lempung Terhadap Kuat Geser Tanah - Khairul Umam; Soewignjo Agus Nugroho; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Clayey sand’s shear strength is influenced by several factors, for examples sand and clay soil fraction, soil properties, density, moisture content, and gradation. Sand and clay mixture with same composition may different in shear strength. It is influenced by moisture content, density and gradation. This research aims to study the effect of clay content in sand that change the Shear strength of soil. Variation of clayey sand soil distinguished based on percentage, every variation have different gradation from well-graded sand to poorly-graded sand. Each sample variation is mixed with a certain moisture content, preloading created in order to represent overburden pressure. Samples was tested of gradation, density and shear strength. Relationship between gradation and shear strength value expressed by the value of Cc, Cu and cohesion, internal friction angle shows specific graphs in particular trends. The results showed effect of gradation and density on soil shear strength. Soil with well-graded sand and dense has good shear strength, in the other hand shear strength decreased when the gradation and density became lower. The addition of clay will increase cohesion and decrease internal friction angle.Keywords : clay, density, gradation, shear strength, sand.